The Ethics of Armed Humanitarian Intervention - SCHEID, Don E. (Cambridge University Press, 2014)
The question of military intervention for humanitarian purposes is a major focus for international law, the United Nations, regional organizations such as NATO, and the foreign policies of nation. Against this background, the 2011 bombing in Libya by Western Nations has occasioned renewed interest and concern about armed humanitarian intervention and the doctrine of responbility to protect.